2005
DOI: 10.1002/eji.200425556
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulator FTY720 interferes with effector functions of human monocyte‐derived dendritic cells

Abstract: The potent immunomodulator FTY720 elicits immunosuppression via acting on sphingosine 1-phosphate receptors (S1PR), thereby leading to an entrapment of lymphocytes in the secondary lymphoid tissue. To elucidate the potential in vitro effects of this drug on human monocyte-derived DC, we used low nanomolar therapeutic concentrations of FTY720 and phosphorylated FTY720 (FTY720-P) and investigated their influence on DC surface marker expression, protein levels of S1PR and DC effector functions: antigen uptake, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
105
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 38 publications
10
105
1
2
Order By: Relevance
“…Additionally, the disruption of the IL-10 suppressive and regulatory pathway does not allow to relate FTY720 action to differentiation-inducing capacities. Only if this activity of FTY720 could be exerted, an enhanced generation of tolerogenic DC cells might lead to an induction of Treg, which-as mentioned above-has already been suggested in several in vitro studies before (27,28).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Additionally, the disruption of the IL-10 suppressive and regulatory pathway does not allow to relate FTY720 action to differentiation-inducing capacities. Only if this activity of FTY720 could be exerted, an enhanced generation of tolerogenic DC cells might lead to an induction of Treg, which-as mentioned above-has already been suggested in several in vitro studies before (27,28).…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, S1P modulates the DC-mediated T cell response in favor of Th2 lymphocyte-dominated immunity, i.e., the suppression of IL-12 and enhancement of IL-10 production by S1P-treated DC was associated with a Th1 to Th2 switch of an in vitro primed T cell response (31). To extend these findings regarding S1P toward FTY720 Muller et al (27) clearly showed that in vitro treatment of monocyte-derived DC with therapeutic concentrations of FTY720 and FTY720-P led to a significant change of the cytokine production profile of DC from high IL-12/low IL-10 to low IL-12/high IL-10 production, thus also biasing T cell responses toward Th2 or Treg. This shift from high IL-12/low IL-10 to low IL-12/high IL-10 following treatment with FTY720 indicative for DC targets could also be observed in our in vivo system of TNBS colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of lymphocytes was reduced in peripheral lymphoid organs but was increased in secondary lymphoid organs, such as the lymph nodes and Peyer's patches (47). However, more recent investigations indicated that the action of FTY720 leads to a significant change in the cytokine-production profile of DCs from IL-12 high IL-10 low to IL-12 low IL-10 high , thus biasing T cell responses toward Th2 cells or Tregs (48). Other recent studies (49,50) showed that a S1P1-directed agonist could dampen CNS inflammation in a plasmacytoid DC-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…41 FTY720 also modulates dendritic cell (DC) functions [41][42][43][44] ; among those, DC migration and endocytosis are suppressed via an effect on S1P 3 . 41 Sequestration of lymphocytes in secondary lymphoid organs prevents the cells from trafficking to the tissues target of inflammation.…”
Section: Fingolimod (Fty720)mentioning
confidence: 99%